Attitudes, beliefs, and knowledge regarding medical cannabis among healthcare students in the Republic of Cyprus: a cross-sectional descriptive correlational study - Sokratous, Sokratis; Mpouzika, Meropi; Kaikoushi, Katerina; Alexandrou, George; Karanikola, Maria (My University, 2023)
Although international research-based literature from the last 2 decades seems to favor the use of medical cannabis (MC), there is a lack of evidence concerning healthcare students' education on MC in the Republic of Cyprus and across the world. Therefore, this study explores healthcare students' attitudes, beliefs, and knowledge regarding the use of MC. We paid special attention to differences across specific sociodemographic (gender, age, and religion status) and educational (level of study and study field) characteristics.
Keywords: attitudes; beliefs; Cyprus; healthcare students; knowledge; medical cannabis